Agreement regarding the presentation of the verses of the faith between Surat Al- Anfal and Al- Hijr - daradkah, Raja Mohammad (Journal of Islamic Sciences, 2022)
The aim of this research is to identify the method of the Noble Qur’an in presenting the verses of faith in the surat Al- Hijr and surat Al- Anfal. The research attempted to answer the two questions: 1) What are the aspects of the contractual agreement between Surat Al- Hijr and Surat Al- Anfal? 2) What are the topics for which the verses of the doctrine were mentioned in both Surat Al- Hijr and Surat Al- Anfal? The researcher used the inductive approach by tracking and collecting the verses that talk about “the verses of the doctrine in Surat Al- Anfal and Surat Al- Hijr", the researcher also used the analytical and reasoning approach represented in stating, interpreting and analyzing of the verses that talked about the aspects of the contractual agreement between Surat Al- Anfal and Surat Al- Hijr. It has been found through the research that there is agreement in presenting certain doctrinal axes in Surat Al- Anfal and Surat Al- Hijr, although the approach of both of them surah differs in presenting the doctrinal aspects regarding the characteristics of the Meccan and Medinan surah.